Risk Control of Moon Orchid Production Using FMEA Method and Fishbone Diagram - Zumi Saidah; Nur Syamsiah; Abhyasa Hardhiawan (Jurnal Penelitian Pendidikan IPA, 2022)
One type of orchid that is known to the public is the type of Phalaenopsis amabilis or the moon orchid. Orchid cultivation is inseparable from production risks that are influenced by internal and external factors. This risk allows the occurrence of an event that may cause losses. This study aims to identify sources of risk, analyze sources of risk priority management, and propose actions to control the production of Orchid Bulan. This research was conducted by Salsa Orchid, located in Cihideung Village, Parongpong District, West Bandung Regency, West Java Province. Identification and analysis of the impact of the risks posed are analyzed using the Failure Mode and Effect Analysis (FMEA) method, while to analyze the source of risk that is a priority for treatment is analyzed using a Fishbone Diagram. The study results show that critical values that must be addressed immediately are insufficient sunlight, too close spacing, low level of labor discipline, and less strategic production locations. The proposed handling of the risk of lack of sunlight is carried out by adjusting the intensity of light from the existing shade according to the needs of the moon orchids. Spacing that is too close is overcome by rearranging the position of the spacing so that the orchid leaves do not cover one another. The low level of labor discipline is overcome by intensive supervision of the work and employee work results. Production locations that are not strategic are overcome by using air conditioners and blowers to regulate air circulation, temperature, and humidity in the greenhouse